STATE AND RELIGIOUS ASSOCIATIONS IN KAZAKHSTAN: LEGAL REGULATION AND POLITICAL CONTEXT - PODOPRIGORA, Roman; KASSENOVA, Nargis (CENTRAL ASIA AND THE CAUCASUS, 2017)
The article discusses the main features of the social, political, and legal status of religious associations in contemporary Kazakhstan. The data from sociological studies and the analysis of state policy and legislation allow for the conclusion that the ongoing religious revival and an increase in the number of religious associations in the post-Soviet period have not led to a significant growth in the religiosity of Kazakhstani society or a dramatic change in the role of religion and religious associations in political and public life. Nevertheless, after a certain period of liberalization (1991-2004), the state resumed tough control over the religious sphere and re-installed constraints on the public activity of religious structures. This change was triggered, among other factors, by the politicization of religion, mainly associated with Islamic associations or movements that are unrecognized or banned in Kazakhstan. Despite the principle of separation of religion from the state stipulated in the legislation, the state develops its own policy in the religious sphere aimed at consolidating the secularity of Kazakhstani society. However, this consolidation—in the manner it occurs in Kazakhstan—is accompanied by pressure on believers and religious associations, the majority of which distance themselves from any political activity. The state also creates unequal opportunities for religious associations, cultivating the privileged status of the Spiritual Board of the Muslims of Kazakhstan and the Russian Orthodox Church in Kazakhstan to gain more legitimacy for the system in both its domestic and foreign policy.